Correction: A nature-inspired lubricant-infused surface for sustainable drag reduction. Issue 42 (21st October 2019) - Lee, Sang Joon; Kim, Hae Nyeok; Choi, Woorak; Yoon, Gun Young; Seo, Eunseok
Abstract : Correction for 'A nature-inspired lubricant-infused surface for sustainable drag reduction' by Sang Joon Lee et al., Soft Matter, 2019, DOI: ; 10.1039/c9sm01576k .